Rapid induction of preneoplastic liver foci in embryonal turkey liver by diethylnitrosamine - Enzmann, Harald G.; Kühlem, Christiane; Kaliner, Georg; Löser, Eckhard; Bannasch, Peter (Toxicologic pathology, 1995)
Diethylnitrosamine (DEN) was injected into fertilized turkey eggs. After incubation for 24 days, the livers of the embryos were removed and investigated by means of histological and enzyme-histochemical methods. Doses of 2 and 5 mg DEN per egg had no effect on mortality and embryo weight but induced various types of foci of altered hepatocytes. In addition, a replacement of the trabecular structure of the liver by a tubular arrangement of the hepatocytes and markedly enlarged hepatocytes were found. The diethylnitrosamine-induced foci of altered hepatocytes were very similar to the preneoplastic lesions that occur in the liver of mammals during hepatocarcinogenesis and are regarded as early indicators of carcinogenicity. The presented in ovo model is a simple (1 dose), rapid (24 days), and inexpensive (no animal housing) approach for the induction of foci of altered hepatocytes. The sensitivity of this carcinogenesis bioassay appears to be comparable to that of lifetime studies in rodents. It is proposed that the induction of preneoplastic foci of altered hepatocytes in ovo is a valuable screening model for hepatocarcinogenic effects.
Gesehen am 13.12.2023